Огляд досягнень в області електролітно-плазмового полірування виробів з титанових сплавів - Негруб, Світлана Леонідівна; Володько, Євгеній Григорович (НТУ "ХПІ", 2017)
У даному огляді систематизовані відомості про сучасний метод фінішної обробки поверхні виробів із титанових сплавів – електролітно-плазмове полірування (ЕПП). Розглянуті дослідження технології, механізм формування поверхневого шару при обробці, система електроліт-плазма-метал та її особливості, основні уявлення про процес ЕПП та його механізми, проведений порівняльний аналіз наукових досягнень електролітно-плазмового полірування поверхні сталевих та титанових виробів (електроліти, режими, шорсткість поверхні), проаналізована практика електролітно-плазмового полірування.

In this review, systematic information on the current method of surface finishing products from titanium alloys – electrolytic-plasma polishing (EPP). Reviewed the research on the subject, basic representation of the process EPP and its mechanism, mechanism of surface layer formation during processing, electrolyte-plasma-metal system and its features, carried out comparative analysis of scientific achievements EPP surface of steel and titanium products (electrolytes, regimes, surface roughness), was analyzed practice of electrolytic-plasma polishing. It is shown that, due to lack of experimentally justified scattering ability of the electrolyte at EPP, caring out complex experimental studies of the effect of EPP on such operational characteristics of the surface as corrosion resistance, resistance to intergranular corrosion, coefficient of friction, adhesion strength of galvanic and vacuum-plasma coatings will significantly expand the scope of the application of EPP technologies, nomenclature of processed alloys and increase the reliability of parts and assemblies for various purposes.
Overview achievements in the field electrolytic-plasma polishing products from titanium alloys
Keywords: електроліт; плазма; розряд; технологічний процес; шорсткість поверхні; вольтамперна характеристика; парогазова оболонка; polishing process; surface roughness; current-voltage characteristics; vapor-gas shell